Manajemen Konflik di Lembaga Pendidikan - Bashori, Bashori (Institut Agama Islam Negeri Lhokseumawe, 2018)
Planning occupies an important position in an institution or institution, which determines the initial movement of an institution. Therefore an institution will progress and produce maximum goals, Planning is an activity to determine goals and formulate and regulate the utilization of resources: information, finance, methods and time followed by decision making and explanations about achieving goals, determining policies, determining programs, determination of certain methods and procedures and determination of the schedule for the implementation of activities. In the basic principles of Islamic education management planning, the Koranic perspective is divided into two general principles of planning and operational technical principles.